An exploratory study on the aspects of vocabulary knowledge addressed in EAP textbooks - Vu, Duy Van; Michel, Marije (Dutch Journal of Applied Linguistics, 2021)
Vocabulary knowledge, which plays an important role in foreign or second language (L2) learning, involves a range of aspects such as form and meaning, grammatical functions, or word parts. Little research, however, has investigated how aspects of vocabulary knowledge are addressed in L2 textbooks. This study aims to fill that gap by examining the aspects of vocabulary knowledge that English for Academic Purposes (EAP) textbooks pay attention to. To that end, four EAP textbooks of upper-intermediate and advanced levels were investigated. A total of 873 vocabulary activities were identified and analysed based on Nation (2013) and Brown’s (2011) frameworks. Results show that grammatical functions, associations, and word parts receive the most attention in the EAP textbooks while written form, constraints on use, and spoken form receive the least attention. The findings also demonstrate variations among the EAP textbooks in their amounts of attention to different aspects of word knowledge.